Foliar Spraying with Compound Amino Acid-Iron Fertilizer Increases Leaf Fresh Weight, Photosynthesis, and Fe-S Cluster Gene Expression in Peach (Prunus persica (L.) Batsch). (27th May 2020) - Sheng, Yuting; Cheng, Hao; Wang, Limin; Shen, Jingyuan; Tang, Meiling; Liang, Meixia; Zhang, Kai; Zhang, Hongxia; Kong, Qun; Yu, Mingliang; Song, Zhizhong
Abstract : As one of the most important micronutrients, iron (Fe) plays a critical role in various metabolic processes during plant growth and development. However, the molecular mechanisms towards Fe metabolism and nutrition in fruit trees are largely unknown. In this study, we examined the effects of amino acid-Fe compound fertilizer spraying on leaf development in peach ( Prunus persica (L.) Batsch) at different developmental stages. Foliar spraying with amino acid-Fe compound fertilizer did not cause any significant changes in leaf morphology but remarkably increased leaf fresh weights. Fe concentration, photosynthetic parameter, and Fe-S protein analyses revealed that Fe accumulation, total chlorophyll content, net photosynthetic rate (P N ), and stomatal conductance (g s ), as well as nitrite reductase (NIR) and succinate dehydrogenase (SDH) activities, were significantly higher in the leaves sprayed with amino acid-Fe compound fertilizer than in the control leaves sprayed with distilled water. Further quantitative real-time PCR (qRT-PCR) analyses demonstrated that Fe-S cluster biosynthesis genes were differentially expressed in the leaves at different developmental stages. Foliar spraying with amino acid-Fe compound fertilizer significantly increased the expression of the most tested Fe-S cluster biosynthesis genes. Our findings provide new insights into the understanding of effects of Fe fertilization application on leaf development in perennial woody fruit trees.